Approche clinique et didactique de l'inclusion des élèves porteurs de troubles du comportement - Sylvie Canat-Faure; Capucine Huet
This article is based on interviews and observations of teachers in the one hand and kids with behavioural disorders in the other hand. The aim is to propose a clinical and didactical approach of obstacles within the classroom to demonstrate that inclusiveness requires to take into account special scaffholding needs for teachers as much as for students. Authors address an in-between posture and transitional phenomenon as key elements to offer secured learning situations and contexts. Inclusiveness at stake summons scaffholded frameworks to support learning processes for students and their teachers.